Sistema de gerenciamento de energia para unidades de geração distribuída com múltiplos inversores - Piveta, Marcelo (2024)
This work proposes an Energy Management System (SGE) for Distributed Generation (GD) units composed of multiple inverters and connected to medium voltage distribution systems. The EMS aims to optimize the dispatch of the DG unit, prevent occurrences of excessive overvoltage at the common connection point (PCC), and maximize the profits of the DG unit owner. The dispatch optimization is achieved through minimizing a performance index using a Particle Swarm Optimization (PSO) algorithm. The proposed performance index is one of the main contributions of this work, as it allows the minimization of voltage regulation costs at the CCP by financially weighting the use of active and reactive power. Moreover, during operational periods with voltage within limits, the proposed performance index enables the correction of the power factor (FP) of the DG unit, thus avoiding penalties. Another contribution of this work is the design of the EMS for applications in DG units with multiple inverters, allowing the simultaneous optimization of dispatch for several converters under non-uniform operational conditions. Mathematical analyses and real-time emulations are presented to validate the proposed EMS. The obtained results demonstrate that the proposed strategy allows voltage regulation and operation cost reduction more effectively than other approaches presented in the literature.